The relative efficiency of investment management of life insurers and takaful operators - Yakob, Rubayah; Yusop, Zulkornain; Radam, Alias; Ismail, Noriszura (Business Perspectives, 2015)
The objective of this study is to analyze the efficiency and determinants of investment management among life insurers and takaful operators and, thus be able to describe their investment efficiency and provide information to firms about the things that need to be improved. This study will use slack-based measure- data envelopment analysis (SBM - DEA) to determine the efficiency of investment management and Tobit analysis in identifying the determinants of the investment management efficiency. The result of SBM - DEA shows that the investment management efficiency of insurers and takaful operators was moderate. The heterogeneity of investment management efficiency declined during the study period and this is particularly encouraging because it shows that the insurers and takaful operators are converging towards the best practices. Besides, the result also reveals that the inefficiencies in investment management are mostly caused by the failure to manage all the resources at optimum level. Meanwhile, the result from Tobit analysis confirms that operating system and investment-linked product enhance the investment management efficiency of insurers and takaful operators. On the other hand, size does not provide a significant effect on the efficiency of investment management of insurers and takaful operators.